Increased Endoplasmic Reticulum Stress and Decreased Proteasomal Function in Lafora Disease Models Lacking the Phosphatase Laforin - Vernia, Santiago (Public Library of Science, 2009)
BACKGROUND: Lafora progressive myoclonus epilepsy (Lafora disease; LD) is a fatal autosomal recessive neurodegenerative disorder caused by loss-of-function mutations in either the EPM2A gene, encoding the dual specificity phosphatase laforin, or the EPM2B gene, encoding the E3-ubiquitin ligase malin. Previously, we and others have shown that both proteins form a functional complex that regulates glycogen synthesis by a novel mechanism involving ubiquitination and proteasomal degradation of at least two proteins, glycogen synthase and R5/PTG. Since laforin and malin localized at the endoplasmic reticulum (ER) and their regulatory role likely extend to other proteins unrelated to glycogen metabolism, we postulated that their absence may also affect the ER-unfolded protein response pathway. METHODOLOGY/PRINCIPAL FINDINGS: Here, we demonstrate that siRNA silencing of laforin in Hek293 and SH-SY5Y cells increases their sensitivity to agents triggering ER-stress, which correlates with impairment of the ubiquitin-proteasomal pathway and increased apoptosis. Consistent with these findings, analysis of tissue samples from a LD patient lacking laforin, and from a laforin knockout (Epm2a-/-) mouse model of LD, demonstrates constitutive high expression levels of ER-stress markers BIP/Grp78, CHOP and PDI, among others. CONCLUSIONS/SIGNIFICANCE: We demonstrate that, in addition to regulating glycogen synthesis, laforin and malin play a role protecting cells from ER-stress, likely contributing to the elimination of unfolded proteins. These data suggest that proteasomal dysfunction and ER-stress play an important role in the pathogenesis of LD, which may offer novel therapeutic approaches for this fatal neurodegenerative disorder.